The Design of Notion and PhET-Based Interactive Website for Teaching Materials on the Topic of Linear Motion in Senior High School - Syifa, Azurulia Maurilla; Harijanto, Alex; Nuraini, Lailatul (Berkala Ilmiah Pendidikan Fisika, 2024)
The learning process running in the 21st century has been integrated with technology and can be accessed easily anywhere and anytime. This research aims to describe the results of website design for interactive teaching materials assisted and describe the responses of teachers and students to interactive website teaching materials assisted by Notion and PhET on the topic of linear motion in senior high school. This research uses the Multimedia Development Life Cycle (MDLC) model design to create an interactive design website. There are six steps: concept, design, material collection, manufacture, testing, and distribution with research data collection methods, namely by conducting interviews, observation, documentation, and questionnaires. Based on research, the design of an interactive teaching material website with the help of Notion on the topic of linear motion received a really good response from teachers and students and can be used for learning in senior high school.